Strategic, Tactical, and Internal Green Marketing Orientations: The Role of Perceived Value in Building Sustainable Customer Loyalty - He, Qilin (Transactions on Economics, Business and Management Research, 2024)
Green marketing has emerged as a vital strategy for businesses to align with the growing environmental consciousness of consumers. This study explores how three types of green marketing orientations—strategic, tactical, and internal—influence customer loyalty through the mediating role of perceived value. By integrating these orientations, companies can enhance their environmental credibility, increase consumer loyalty, and create lasting business value. Using data from 301 participants across various industries in China, this research employed regression analysis and structural equation modeling (SEM) to test the relationships between these orientations, perceived value, and customer loyalty. The findings demonstrate that all three orientations significantly impact customer loyalty, with perceived value playing a crucial mediating role. The study offers important implications for companies seeking to enhance their green marketing strategies to drive both sustainability and business objectives.